Use of CT simulation and 3-D radiation therapy treatment planning system to develop and validate a total-body irradiation technique for the New Zealand White rabbit. (3rd December 2021) - Poirier, Yannick; Prado, Charlotte; Prado, Karl; Draeger, Emily; Jackson, Isabel L; Vujaskovic, Zeljko
Abstract: Purpose: Well-controlled ionizing radiation injury animal models for testing medical countermeasure efficacy require robust radiation physics and dosimetry to ensure accuracy of dose-delivery and reproducibility of the radiation dose-response relationship. The objective of this study was to establish a simple, convenient, robust and accurate technique for validating total body irradiation (TBI) exposure of the New Zealand White rabbit. Methods: We use radiotherapy techniques such as computed tomography simulation and a 3 D-conformal radiation therapy treatment planning system (TPS) on three animals to comprehensively design and preplan a TBI technique for rabbits. We evaluate the requirement for bolus, treatment geometry, bilateral vs anterior-posterior treatment delivery, the agreement between monitor units calculated using the TPS vs a traditional hand calculation to the mid-plane, and resulting individual organ doses. Results: The optimal technique irradiates animals on the left-decubitus position using two isocentric bilateral parallel-opposed 6 MV x-ray beams. Placement of a 5 mm bolus and 8.5 mm beam spoiler was shown to increase the dose to within ≤5 mm of the surface, improving dose homogeneity throughout the body of the rabbit. A simple hand calculation formalism, dependent only on mid-abdominal separation, could be used to calculate the number of monitor units (MUs) required to accurately deliver the prescribed dose to the animal. For the representative animal, the total body volume receiving > 95% of the dose, V95% > 99%, V100% > 95%, and V107% < 20%. The area of the body receiving >107% of the prescribed dose was mainly within the limbs, head, and around the lungs of the animal, where the smaller animal width reduces the x-ray attenuation. Individual organs were contoured by an experienced dosimetrist, and each received doses within 95–107% of the intended dose, with mean values ∼104%. Only the bronchus showed a maximal dose >107% (113%) due to the decreased attenuation of the lungs. To validate the technique, twenty animals were irradiated with four optically-stimulated luminescence dosimeters (OSLDs) placed on the surface of each animal (two on each side in the center of the radiation beam). The average dose over all animals was within <0.1% from intended values, with no animal receiving an average dose more than ±3.1% from prescription. Conclusion: The TBI technique developed in this pilot study was successfully used to establish the dose-response relationship for 45-day lethality across the dose-range to induce the hematopoietic-subsyndrome of the acute radiation syndrome (ARS).